Technical Characteristics in the Diffusion of Cleaner Residential Heating System in China: The Case of Air-Source Heat Pump Technology. (June 2019) - Su, Dejin; Zhou, Wenli; Du, Qixia; Huang, Yongchun
This study aims to explore the technical characteristics that affect user satisfaction with air-source heat pump technology which is recognized as one typical cleaner residential heating system and being promoted in China in response to the national "coal to electricity" policy. Moderated hierarchical linear regression analysis was conducted to analyze data from a questionnaire survey of 256 residents in suburban Beijing. Empirical results indicated that product convenience, product design, product reliability, product knowledge, and total cost, respectively, affect user satisfaction, but product safety has no significant effect on user satisfaction. Meanwhile, total cost is an important contingent factor that might weaken the positive effects of product convenience (or product design) on user satisfaction. Our research provides empirical evidence for identifying factors that influence user satisfaction with cleaner residential heating system in response to new energy policy and further provides useful managerial implications for market practice.